2015
DOI: 10.1152/jn.00145.2015
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of error-sensitivity during a prism adaptation task in people with cerebellar degeneration

Abstract: S. Modulation of error-sensitivity during a prism adaptation task in people with cerebellar degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…We found that selective reward facilitated saccade adaptation by increasing adaptation speed in one direction and not the other. Thus, although reward motivation is not necessary to induce saccade adaptation per se (Frens and van Opstal, 1994; Hopp and Fuchs, 2004), it apparently can speed that adaptation by increasing the sensitivity to the error in driving adaptation, i.e., how much the brain “learns” from a given error (Marko et al, 2012; Hanajima et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…We found that selective reward facilitated saccade adaptation by increasing adaptation speed in one direction and not the other. Thus, although reward motivation is not necessary to induce saccade adaptation per se (Frens and van Opstal, 1994; Hopp and Fuchs, 2004), it apparently can speed that adaptation by increasing the sensitivity to the error in driving adaptation, i.e., how much the brain “learns” from a given error (Marko et al, 2012; Hanajima et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The experimental procedures were the same as those reported previously . Participants were seated facing a 21‐inch electrostatic touch panel monitor positioned 300 mm from their eyes.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedures were the same as those reported previously. 18,19 Participants were seated facing a 21-inch electrostatic touch panel monitor positioned 300 mm from their eyes. Visual occlusion spectacles with liquid crystal shutters (PLATO, Translucent Technologies, ON, Canada) were set in front of the eyes to prevent visual input from the finger movement during the task performance.…”
Section: Experiments 2: Prism Adaptation Taskmentioning
confidence: 99%
“…included an error-free period, thus permitting robust measurement of error sensitivity and forgetting 836 rates. In all cases, we measured the differences in error sensitivity for small (between 5° and 20°) and 837 large (between 20° and 30°) errors from the start (epoch 1) to the last epoch (epoch 60), predicted by 838…”
mentioning
confidence: 99%